Analisis Perubahan Garis Pantai selama 10 Tahun Menggunakan CEDAS (Coastal Engineering Design and Analisys System) di Perairan Teluk Awur pada Skenario Penambahan Bangunan Pelindung Pantai - Hariyadi Hariyadi (Universitas Diponegoro, 2011)
Abstract Live Environment Mining and Energy Duty Kabupaten Jepara (2006) said Teluk Awur shore is potential area occurred erosion. Reliable attempted to use preventing the problem is protecting with making hard struktur, therefore investigated with modeling shoreline changed use protection structure added three scenarios. The purpose of this study to known shoreline changed and the smallest effect in the scenario of protection structure added. For the efficiency time and price, so that prediction and simulation is done with using numeric model method with GENESIS (GENEralized model for SImulating Shoreline change). GENESIS is the one of subprogram in the NEMOS(Nearshore Evolution MOdeling System) at the CEDAS (Coastal Engineering Design and Analisys System) software. Long of the model simulation area is 8720 meters. Model simulation use three scenarios are Detached Breakwater, Non Diffracting Groin, and Detached Breakwater and combination of Non Diffracting Groin. and Detached Breakwater. Shoreline changed can consider based on simulation result is sediment transport volume, erosion wide, sedimentation and long shoreline changed. Based on result simulation, shoreline changed in existing condition is the most if compared with the other scenario with values-93.5942 meters, the smallest values occurred at the combination scenario from Detached Breakwater and Non Diffracting Groin with -54.3157 meters. This result give the information that protection structure required to decrease shoreline changed occur. Key Words: Shoreline Change, CEDAS, NEMOS, GENESIS, Teluk Awur, Detached Breakwater, Non Diffracting Groin